Comparative Genomics Reveals a Burst of Homoplasy-Free Numt Insertions. (31st May 2018) - Liang, Bin; Wang, Ning; Li, Nan; Kimball, Rebecca T; Braun, Edward L
Abstract: Mitochondrial DNA sequences are frequently transferred into the nuclear genome, giving rise to numts ( nu clear m i t ochondrial DNA segments). In the absence of whole genomes, avian numts have been suggested to be rare and relatively short. We examined 64 bird genomes to test hypotheses regarding numt frequency, distribution among taxa, and likelihood of homoplasy. We discovered 100-fold variation in numt number across species. Two songbirds, Geospiza fortis (Darwin's finch) and Zonotrichia albicollis (white-throated sparrow) had the largest number of numts . Ancestral state reconstruction of 957 numt insertions in these two species and their close relatives indicated a remarkable acceleration of numt insertion in the ancestor of Geospiza and Zonotrichia followed by slower, continued accumulation in each lineage. These numts appear to result primarily from de novo insertion with the duplication of existing numts representing a secondary pathway. Insertion events were essentially homoplasy-free and numts appear to represent perfect rare genomic changes.